Evaluasi Kinerja Perusahaan Perbankan Sebelum dan Sesudah menjadi Perusahaan Publik di Bursa Efek Jakarta (BEJ) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Through an initial public offering (IPO) a firm going public will raise funds or cash which can be to help finance its operations. An IPO is expected to improve the performance of a firm. Numerous studies examining of IPOs on the Jakarta Stock Exchange (JSX) document a positive impact on company performance, but others show inconsistent results. This research investigates whether there is any significant difference in a bank's performance before and after going public. Bank performance is measured using CAMEL rating, which is commonly used to identify changes in bank performance. In this research bank performance is evaluated based on five aspects: capital adequacy, asset quality, management, earnings, and liquidity. To this end, this research employs an empirical study using 22 sample banks. Purposive sampling is obtained from 25 bank listed on the JSX. Historical data is provided by annual financial statements of banks as per December 31. The results of this research are expected to answer the question "Does bank performance improve after going public?" Two statistics tools are used in this research. Wilcoxon Signed Rank Test is used to test the difference between bank performance before and after listing, investigating the partial variables of bank performance. The Manova test is used to assess the overall difference in bank performance before and after listing. The empirical results show that although some of the financial CAMEL ratios show significant differences, these are temporary and inconsistent. Only CAR returns a statistically significant difference before and after listing for a tree time period test. The results of this research conclude that bank performance does not change after a bank floats its shares on the stock market. This finding is consistent with Wijaya (1997). In other words, funds raised from IPOs do not improve bank performance.